Tunable Luminescence of Ce3+/Eu2+ Activated in Single-Phase Li2BaSiO4 Phosphor via Energy Transfer. (9th September 2021) - Pei, Qiangsheng; Chen, Lei; Du, Fu; Xiao, Yanfei; Peng, Jiaqing; Ye, Xinyu
Abstract : A series of Ce 3+, Eu 2+ co-doped Li2 BaSiO4 cyan-green phosphors were synthesized by a high temperature solid phase method. The crystal structure, morphology, luminescent properties and temperature characteristics of the corresponding samples were systematically studied. The main peaks of the emission spectra of Li2 BaSiO4 :Ce 3+, Eu 2+ were shifted from 400 nm to 500 nm by adjusting the Ce 3+, Eu 2+ co-doping concentration. And a series of phosphors with continuous changes from blue to cyan green were obtained, which effectively compensated for the gap between the white LED at 470–510 nm region. The energy transfer efficiency and mechanism of Ce 3+, Eu 2+ in Li2 BaSiO4 were studied by fluorescence lifetime. The highest energy transfer efficiency was 46.01%, and the energy transfer mechanism was determined to be electric dipole-electric dipole transition. Finally, fabricating a white LED device which coated blue, green-yellow, red and as-prepared cyan phosphors on the surface of ultraviolet chip (350 nm), and the device exhibited excellent luminescence characteristics (Ra = 95.2, CCT = 3105 K). The results show that the Li2 BaSiO4 :Ce 3+, Eu 2+ phosphor developed can be regard as single-component tunable color luminescent materials under the excitation of near ultraviolet light.